"CULTURAL CODES" IN THE STUDY OF SOMATIC PHRASEOLOGICAL UNITS (Scientific journal of the Fergana State University, 2023)
This article focuses on the study of somatic phraseology through cultural codes, which allows you to see the basic factors in Uzbek, Russian and English languages. Categorizing somatic phraseology, my explanations, how somatism is represented by different cultural codes in different areas. The discovery of the nature of somatism through cultural codes showed that every nation has its own characteristics.